Dietary Management of Obesity - Sang Hoon Lee; San Ha Kim; Sung Chul Park (The Korean Journal of Gastroenterology, 2024)
Obesity is defined as a condition characterized by the abnormal accumulation of fat cells, which results in increased body weight. Worldwide, obesity is progressively on the rise, leading to an increased prevalence of chronic conditions such as cardiovascular disease, type 2 diabetes, and hyperlipidemia. Obesity is a result of the interplay between genetic, metabolic, social, behavioral, and cultural factors, necessitating an interdisciplinary and multimodal management approach. Diet therapy, which includes dietary modifications and nutritional interventions, is a fundamental component of the multifaceted approach to managing obesity. The principle of diet therapy is based on achieving weight loss through a negative energy balance and maintaining weight through an equilibrium of energy intake and expenditure. Strategies for weight loss and control rely on caloric restriction, macronutrient distribution, and dietary patterns such as the Mediterranean and Dietary Approaches to Stop Hypertension (DASH) diets. Recently, studies have been conducted on weight control using information and communication technology-based interventions, as well as interventions based on intestinal microorganisms which consider inter-individual variability and long-term adherence. In conclusion, diet therapy stands as a pivotal element in the management of obesity, providing a personalized and comprehensive approach to weight control. By combining evidence-based dietary strategies with behavioral modifications and consistent support, healthcare professionals can enable individuals to attain and sustain a healthier weight, thereby reducing related health risks.